Disentangling the effects of flipped classroom instruction in EFL secondary education: When is it effective and for whom?. (October 2021) - Wagner, Marlene; Urhahne, Detlef
Abstract: Flipped classroom refers to an instructional approach in which students study educational videos at home and do homework assignments in class. The present study aims to compare flipped classroom with other forms of video-based instruction and determine which types of students benefit most from video-based instruction. Thirty-eight EFL school classes with 848 ninth-grade students took part in a quasi-experimental pre-post-test intervention study over four weeks. Two independent variables were completely crossed resulting in four experimental conditions: video (at home vs. in class) and instructional method (student-centred vs. teacher-centred). Multilevel analysis reveals that all four experimental conditions were equally effective in promoting students' learning gains. At-risk, average and excellent students profited least from the learning conditions. The study constitutes a first step towards a comprehensive evaluation of flipped classroom by using a better-controlled research design and may contribute to a more objective discussion about the positive effects of flipped classroom. Highlights: Use of instructional video was compared in flipped class and in-class models. A four-week intervention study with four experimental conditions was conducted. All four experimental conditions were equally effective in promoting achievement. Confident and independent students profited most from the learning conditions. The study may contribute to a more objective discussion about the flipped classroom.